Cultivar ideotype for intensive olive orchards: plant vigor, biomass partitioning, tree architecture and fruiting characteristics - Rosati, Adolfo; Paoletti, Andrea; Lodolini, Enrico Maria; Famiani, Franco (Frontiers in Plant Science, 2024)
In order to achieve higher and earlier yield, modern olive orchards are increasingly intensified, with tree densities up to > 1500 trees hectare-1. With increasing tree densities, individual-tree canopy volume must be proportionally reduced. Not all cultivars are adaptable to high and very high orchard densities, because of excessive vigor and/or insufficient bearing when the canopy is pruned to a small volume. However, what makes an olive cultivar suitable for intensive and super intensive orchards is not clear. Recently, few studies have addressed this topic, suggesting that tree architecture and early bearing are essential traits. Yet, what architectural and productive features are important, how they work and whether they are interrelated remains elusive. This review summarizes and interprets the literature on olive, as well as the more abundant literature available for other fruit species, aiming to provide a comprehensive knowledge framework for understanding how tree architectural characteristics, plant vigor, and fruiting vary across olive genotypes, and how they are interconnected. It is concluded that, among the architectural characteristics, greater branching and smaller diameters of woody structures are particularly important features for cultivar suitability to intensive and super intensive olive orchards. Greater branching allows to produce more fruiting sites in the small volume of canopy allowed in these systems. It also reduces investments in woody structures, liberating resources for fruiting. Additional resources are liberated with smaller structure diameters. Greater branching also increases resources by increasing biomass partitioning into leaves (i.e. the photosynthetic organs), relative to wood. Since yield is affected by the competition for resources with vegetative growth, reducing resource investments in woody structures and/or increasing resource directly, increases yield. Yield, in turn, depresses vegetative growth, reducing vigor and the need for pruning. High yields also produce short shoots which have relatively greater investments in leaf mass and area, and lower in the woody stem, making them more suitable than long shoots to support concurrent fruit growth. This single framework of interpretation of how the different architectural and fruiting characteristics work and interact with one-another, will provide guidance for cultivar selection and breeding for intensive and super intensive olive orchards.